Exoskeletons: Productivity and ergonomics in logistics:a systematic review - Victor Kaupe; Carsten Feldmann; Heiko Wagner (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: Exoskeletons are robotic wearables that have the potential to positively support employees during physical working operations. However, the technology is rather young, and long-term studies that could positively influence exoskeletons with respect to health, productivity, and ROI (and thereby support investment in it) are lacking. Accordingly, logistics companies are cautious about investing in exoskeletons. This paper identifies the research gaps that should be addressed in further research to change this situation. Methodology: Based on an extensive literature review following the systematic approach of vom Brocke et al. (2009), this paper surveys current research regarding the impact of exoskeletons in intralogistics with respect to productivity and health. Findings: Since exoskeletons in industrial contexts have been used mainly in pilot trials so far, few findings from long-term studies are available. Accordingly, the sustainable positive influence of exoskeletons on productivity and health cannot be empirically proved. Originality: This paper identifies research gaps for a novel technology that could transform a sector which is characterized by a high proportion of manual labor, a high age average, a shortage of skilled workers, and beside increasing complexity.
urn:nbn:de:gbv:830-882.0161843; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Innovation management; technology management